Implementasi Standar Pengelolaan untuk Peningkatan Mutu Layanan Pembelajaran Pada SMAN 1 Nagrak Sukabumi dan SMAS Pasundan Bandung - Panji Pratama; Hendra Yulianto; Ujang Cepi Berlian; Yosal Iriantara (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2021)
This study aims to test the quality of school services during the COVID-2019 pandemic, especially through an analysis of management standards that apply in schools. This study used a descriptive-qualitative method with a sample of two schools, namely SMAN 1 Nagrak Sukabumi Regency and SMA 3 Pasundan Bandung. In this study, the authors found that the quality of school services was not significantly affected by the COVID-19 pandemic when analyzed from the applicable management standards.